Colouring graphs with no induced six-vertex path or diamond - Goedgebeur, Jan; Huang, Shenwei; Ju, Yiao; Merkel, Owen (Theoretical computer science, 2023)
The diamond is the graph obtained by removing an edge from the complete graph on 4 vertices. A graph is (P6, diamond)-free if it contains no induced subgraph isomorphic to a six-vertex path or a diamond. In this paper we show that the chromatic number of a (P6, diamond)-free graph G is no larger than the maximum of 6 and the clique number of G. We do this by reducing the problem to imperfect (P6, diamond)-free graphs via the Strong Perfect Graph Theorem, dividing the imperfect graphs into several cases, and giving a proper colouring for each case. We also show that there is exactly one 6-vertex-critical (P6, diamond, K6)-free graph. Together with the Lovász theta function, this gives a polynomial time algorithm to compute the chromatic number of (P6, diamond)-free graphs. •We obtain an improved bound on the chromatic number of (P6, diamond)-free graphs.•We show that there is one 6-vertex-critical (P6, diamond, K6)-free graph.•We give a polynomial-time algorithm to colour (P6, diamond)-free graphs optimally.